PENILAIAN DAYA TARIK WISATA KAWASAN AIR TERJUN MANANGGAR DI DESA ENGKANGIN KECAMATAN AIR BESAR KABUPATEN LANDAK - Akbar, Ya’ Muhammad Arsyil; Nugroho, Joko; Widiastuti, Tri (Universitas Tanjungpura, 2014)
The purpose of this study is to provide an assessment of the potential tourist attraction located in zona Mananggar waterfall. This research was conducted with descriptive method, which explains all the potential objects of reseacrh that has been observed and analyzed were based on the Standard Assessment and Development Raw Nature Objects Issued by the Commission for Assessment and Development Cooperation Nature Objects 1993. The results of the overall attractiveness of 160 elemnts. This value is multiplied by the weight value for attractiveness criteria area of 160 x 6 = 960, compared with the Object element Classification of Natural Ecotourism Development. Waterfalls Mananggar has good appeal ( B ) which, when developed into a nayutal attraction, especially when supported interactive collaboration between government and society Key words : Â Tourism potential, data assessment standard, ecotourism